The effect of laser and dynamic quadripolar radiofrequency therapies on the expression of collagenogenesis proteins in the vaginal epithelium and tissue elasticity in women with genital prolapse - Yulia E. Dobrokhotova; Elena N. Kareva; Igor I. Grishin; Natalia A. Kochina; Ekaterina V. Krasnoshchok; Vladimir I. Komagorov (Гинекология, 2023)
Background. Genital prolapse dramatically affects the quality of life of patients. Various sources show that the relapse rate after surgical treatment is 30 to 60%.